Improving Community Resilience on the Lembang Fault: Local Wisdom as the Basis for Innovative Volunteer Communication Strategies for Disaster Mitigation - Dina Ruslanjari; Mochamad Iqbal; Hermin Indah Wahyuni (AIBPM Publisher, 2025)
This study aims to analyze the role of volunteers in innovative communication strategies based on local wisdom. A qualitative descriptive method was used through observation, interviews, and document review in Lembang District, West Bandung Regency. The results of the study show that the Lembang Disaster Management Volunteers (RPBL) developed three communication innovation programs based on local wisdom: the Pelesir Jauh Tina Mamala, the Kelasmina, and the Susur Sesar Mikawanoh Lembur, which integrates the concept of